2017
DOI: 10.3390/rs9060599
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Chlorophyll Fluorescence Parameters Using the Joint Fraunhofer Line Depth and Laser-Induced Saturation Pulse (FLD-LISP) Method in Different Plant Species

Abstract: Abstract:A comprehensive evaluation of the recently developed Fraunhofer line depth (FLD) and laser-induced saturation pulse (FLD-LISP) method was conducted to measure chlorophyll fluorescence (ChlF) parameters of the quantum yield of photosystem II (Φ PSII ), non-photochemical quenching (NPQ), and the photosystem II-based electron transport rate (ETR) in three plant species including paprika (C3 plant), maize (C4 plant), and pachira (C3 plant). First, the relationships between photosynthetic photon flux densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
9
0
1
Order By: Relevance
“…A different approach for stress detection could take advantage of the combination of SiF with different techniques. Rahimzadeh-Bajgiran et al (2017) reported a FLD and laser-induced saturation pulse (FLD-LISP) method as a robust and accurate technique for the estimation of Chl-F parameters such as Φ PSII , NPQ, and ETR, for several plant species. In parallel, a model based on measurements of two satellite detectors (SiF from Orbiting Carbon Observatory-2 and surface reflectance from the moderate resolution imaging spectroradiometer [MODIS]), provided a very sensitive indicator of drought (Zhang et al, 2018).…”
Section: Biotic Stress Detection In High-throughput Platforms and At mentioning
confidence: 99%
“…A different approach for stress detection could take advantage of the combination of SiF with different techniques. Rahimzadeh-Bajgiran et al (2017) reported a FLD and laser-induced saturation pulse (FLD-LISP) method as a robust and accurate technique for the estimation of Chl-F parameters such as Φ PSII , NPQ, and ETR, for several plant species. In parallel, a model based on measurements of two satellite detectors (SiF from Orbiting Carbon Observatory-2 and surface reflectance from the moderate resolution imaging spectroradiometer [MODIS]), provided a very sensitive indicator of drought (Zhang et al, 2018).…”
Section: Biotic Stress Detection In High-throughput Platforms and At mentioning
confidence: 99%
“…The qN shows the part of absorbed radiation that is not used for electron transport in photosynthesis, and besides the conversion of violaxanthin to zeaxanthin in the xanthophyll cycle, the photosystem II subunit S protein (PsbS) protein is also involved in this process [ 35 ]. This parameter increased significantly under the 1 d and 2 d stress but decreased under the 7 d exposure ( Supplementary Materials Figure S2c ).…”
Section: Resultsmentioning
confidence: 99%
“…Another significant advantage of TC‐ODE‐FBA over LC‐ODE‐FBA is its ability to predict the dissipation of excess light energy. The TC‐ODE‐FBA analysis of LL, ML, and HL conditions showed energy dissipation increasing with light intensity (Figure 6a–c) (Nicol et al., 2019; Rahimzadeh‐Bajgiran et al., 2017). The model also predicted a decrease in NPQ in leaves under HL when atmospheric [CO 2 ] increased (Figure 6c,d), which has also been previously established in tobacco (Dahal and Vanlerberghe,2018; Miyake et al., 2005).…”
Section: Discussionmentioning
confidence: 98%